Malnutrition based on mid upper arm circumference and dietary consumption pattern of Lodha tribal children of West Bengal, India - Sabud, Prasanta; Ghosh, Tarapada; Dhar, Arup; Dutta, Sarnali; Bisai, Samiran; Choudhury, Sujata Maiti (International Journal of Research in Medical Sciences, 2020)
Background: Wasting, a form of malnutrition is a major public health burden in developing countries including India. Since, food and diet diversity have direct impact on nutritional status of children. The aim of the study was to assess the dietary consumption pattern and malnutrition based on mid upper arm circumference (MUAC) of Lodha tribal children of Paschim Medinipur and Jhargram districts of West Bengal, India. Methods: A total of 1043 Lodha preschool children (1-5 years) was selected for the present study. MUAC of the children was made and recorded by standard method. A questionnaire for 24-hour dietary recall method was applied to collect dietary information. Dietary diversity was calculated by standard techniques. All statistical analyses were performed by using Statistical package for social sciences (SPSS) software. Results: The mean±SD of MUAC was 129.7±11.3 mm. The results showed that the mean MUAC increased steadily with the advancement of age in both genders. Prevalence of wasting based on MUAC in age-sex combined among Lodha children was 28.9%, of which 24.9% and 4.0% found to be moderate and severe acute malnutrition. The dietary intake of children was insufficient than recommended dietary allowance (RDA). The dietary diversity score (DDS) and Dietary serving score (DSS) of the children were very low. Pearson correlation analysis showed Mean adequacy ratio (MAR) had significant correlation with DDS (r=0.26, p<0.001), DSS (r=0.81, p<0.001), calorie intake (r=0.52, p<0.001) and protein intake (r=0.38, p<0.001). Conclusions: The dietary consumption of Lodha children was inadequate. This effort should be given to improve their nutritional status by nutrition education and nutrient sensitive farming including kitchen garden.